Nitration and amination of polyphenylene oxide: synthesis, gas sorption and permeation analysis - Bhole, Yogesh S.; Karadkar, Prasad B.; Kharul, Ulhas K. (European Polymer Journal, 2007)
A high degree of nitration of polyphenylene oxide (PPO) was successfully achieved by carefully optimizing synthetic protocol. The reduction of nitro group to amino could be done quantitatively. The physical properties of formed polymers were investigated and correlated with gas sorption and permeation properties. The formed polymers were amorphous in nature as revealed by wide angle X-ray diffraction spectra. An increase in the packing density in comparison to unsubstituted PPO as a result of induced polarity was indicated by lowering of fractional free volume and d-spacing. The substitution by either nitro or amino group increased the chain stiffness as revealed by the dynamic mechanical analysis. Though both, nitro and amino group substitution on PPO led to a decrease in pure gas permeability, the selectivity of various gas pairs was increased by these substitutions. The gas sorption analysis revealed that both, solubility selectivity and diffusivity selectivity were increased by these polar group substitutions. The nitro group substitution was more effective in improving solubility selectivity, while amino group substitution was more effective in improving diffusivity selectivity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amination; nitration; permeation; polyphenylene oxide; Sorption

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions

Formal enantioselective synthesis of (-)-epiquinamide by proline-catalyzed one-pot sequential -amination/propargylation of aldehyde and asymmetric dihydroxylation of olefin - Ahuja, Brij Bhushan; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synlett, 2016)
Two independent routes to the formal synthesis of (-)-epiquinamide, have been described: the first route utilizes an l-proline-catalyzed one-pot sequential -amination/propargylation of aldehyde, while the second one employs asymmetric dihydroxylation as the key reaction to install the stereochemistry. While the first synthesis was accomplished in nine steps with 24.4% overall yield and dr 9:1, the second strategy resulted in the synthesis in eight steps with 36.4% overall yield and with perfect enantiocontrol.
Keywords: Amination; diastereoselective; Dihydroxylation; Proline; quinolizidine

Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation